Solid state ion conductor, method for producing the same, positive electrode, negative electrode, negative electrode for lithium secondary battery, and electrochemical cell

CN114976000BActive Publication Date: 2026-10-30SAMSUNG ELECTRONICS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210151453.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-10-05
Filing Date
2022-02-18
Publication Date
2026-10-30
Estimated Expiration
2042-02-18

AI Technical Summary

Technical Problem

可用的硫化物可提供比氧化物大的锂离子传导率,然而,它们也带来安全性忧虑,例如与空气或水反应以放出硫化氢

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003510588520000011
    Figure HDA0003510588520000011
  • Figure HDA0003510588520000012
    Figure HDA0003510588520000012
  • Figure HDA0003510588520000013
    Figure HDA0003510588520000013
Patent Text Reader

Abstract

The present invention relates to a solid ionic conductor, a preparation method thereof, a positive electrode, a negative electrode, a negative electrode for lithium secondary batteries, and an electrochemical cell. The solid ionic conductor comprises a compound of formula (I), wherein M 1 is a cationic element with an oxidation state of +2 or +3; M 2 is a cationic element with an oxidation state of +4 or +5; with the proviso that when M 1 is a cationic element with an oxidation state a of +2, M 2 is a cationic element with an oxidation state of +5, and when M 1 is a cationic element with an oxidation state a of +3, M 2 is a cationic element with an oxidation state of +4; M" is a cationic element with an oxidation state γ, where γ is less than b; X 1 is a cluster anion with an oxidation state of (-1-δ), where δ is 0 or 1; X 2 is a halogen; 0<c≤1; 0≤x≤1; and 0≤y≤2, with the proviso that when M 1 is a cationic element with an oxidation state a of +2 and M 2 is a cationic element with an oxidation state of +5, 0≤y≤1. Li 4+(b‑a)y+cδ+(a‑γ)x M 1 3+x+y M 2 3‑y M" x O 12 X 1 c X 2 1‑c Formula (I).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-reference to related applications

[0002] This application claims priority to, and all benefits arising therefrom, of, U.S. Provisional Patent Application No. 63 / 150,691, filed February 18, 2021, with the United States Patent and Trademark Office, the contents of which are incorporated herein by reference in their entirety. Technical Field

[0003] A solid-state lithium-ion conductor and a method for manufacturing the solid-state lithium-ion conductor are disclosed. A positive electrode including the solid-state lithium-ion conductor, a negative electrode including the solid-state lithium-ion conductor, and an electrochemical cell including the solid-state lithium-ion conductor are also disclosed. Background Technology

[0004] Solid-state lithium batteries offer improved specific energy and energy density, and avoid the safety concerns associated with flammable organic solvents used in liquid electrolytes. Oxide and sulfide solid-state electrolytes have been used. Available sulfides offer higher lithium-ion conductivity than oxides; however, they also raise safety concerns, such as reacting with air or water to release hydrogen sulfide. Oxides offer reduced toxicity relative to sulfides and stability in air, but the application of available oxides is limited by their low conductivity or incompatibility with high-voltage cathode materials or lithium metal.

[0005] Therefore, there remains a need for solid electrolytes that provide improved ionic conductivity and avoid toxicity and safety concerns associated with sulfides. Summary of the Invention

[0006] Solid-state ionic conductors are disclosed, including compounds of formula (I):

[0007] Li 4+(b-a)y+cδ+(a-γ)x M 1 3+x+y M 2 3-y M” x O 12 X 1 c X 2 1-c Formula (I)

[0008] In equation (I), M 1 M is a cationic element with oxidation state a, where a is +2 or +3; 2 M is a cationic element with an oxidation state b, where b is +4 or +5; the condition is that when M 1 When M is a cation element with an oxidation state of +2 a, 2 It is a cationic element with an oxidation state of +5, and when M1 is a cationic element having an oxidation state a of +3, M 2 is a cationic element having an oxidation state of +4; M'' is a cationic element having an oxidation state γ, wherein γ is less than b; X 1 is a cluster anion having an oxidation state of (-1-δ), wherein δ is 0 or 1; X 2 is a halogen; 0<c≤1; 0≤x≤1; and 0≤y≤2, with the proviso that when M 1 is a cationic element having an oxidation state a of +2 and M 2 is a cationic element having an oxidation state of +5, 0≤y≤1.

[0009] Also disclosed is a positive electrode, comprising: a positive electrode active material layer comprising a lithium transition metal oxide, a lithium transition metal phosphate, or a combination thereof; and the solid ionic conductor on the positive electrode active material layer.

[0010] Also disclosed is a negative electrode, comprising: a negative electrode active material layer comprising lithium metal, a lithium metal alloy, or a combination thereof; and the solid ionic conductor on the negative electrode active material layer.

[0011] Also disclosed is a negative electrode for a lithium secondary battery, the negative electrode comprising: a current collector; and the solid ionic conductor on the current collector.

[0012] Also disclosed is an electrochemical cell, comprising: a positive electrode; a negative electrode; and an electrolyte layer between the positive electrode and the negative electrode, wherein at least one of the positive electrode, the negative electrode, or the electrolyte layer comprises the solid ionic conductor. Brief Description of the Drawings

[0013] The following figures show exemplary aspects, in which similar elements are similarly numbered, wherein:

[0014] Figure 1 shows an aspect of a protected positive electrode;

[0015] Figure 2 shows an aspect of a protected negative electrode;

[0016] Figure 3 shows an aspect of a lithium battery;

[0017] Figure 4 is a graph of lithium diffusivity (square centimeters per second, cm 2 / s) versus temperature (K -1 ), which shows the results of Arrhenius analysis for Li5Al4Si2O 12 Br;

[0018] Figure 5 is a graph of lithium diffusivity (cm 2 / s) versus temperature (K) -1 The figure shows Li5Al4Si2O 12 The results of the Arrhenius analysis of Cl;

[0019] Figure 6 Lithium diffusivity (cm) 2 / s) versus temperature (K) -1 The figure shows Li5Al4Si2O 12 The results of I's Arrhenius analysis;

[0020] Figure 7 Lithium diffusivity (cm) 2 / s) versus temperature (K) -1 The figure shows Li5Al4Si2O 12 Results of Arrhenius analysis of BH4;

[0021] Figure 8 Lithium diffusivity (cm) 2 / s) versus temperature (K) -1 The figure shows Li5Al4Si2O 12 The results of SH's Arrhenius analysis;

[0022] Figure 9 Lithium diffusivity (cm) 2 / s) versus temperature (K) -1 The figure shows Li5Al4Si2O 12 Results of Arrhenius analysis of NH2;

[0023] Figure 10 Lithium diffusivity (cm) 2 / s) versus temperature (K) -1 The figure shows Li5Al4Si2O 12 Results of Arrhenius analysis of AlH4;

[0024] Figure 11 Lithium diffusivity (cm) 2 / s) versus temperature (K) -1 The figure shows Li5Al4Si2O 12 Results of Arrhenius analysis of BF4;

[0025] Figure 12 The lithium-ion conductivity (millisiemens / cm, mS / cm) of various sodalite-type materials at 300K versus the anion volume (cubic angstroms, ... (The image is missing from the original text.)

[0026] Figure 13 Displayed Li5Al4Si2O 12Aspects of the crystal structure of BH4 as a solid-state ionic conductor; and

[0027] Figure 14 The plot shows the intensity (arbitrary units, au) versus diffraction angle (degrees, 2θ) for Li5Al4Si2O. 12 Calculated X-ray powder diffraction (XRD) pattern for X (X = Cl, OH, BH4). Detailed Implementation

[0028] Currently available lithium-ion batteries suffer from numerous safety issues due to the leakage and flammability of liquid organic electrolytes, limiting their application in electric vehicles and grid-based energy storage infrastructures. In this context, solid-state batteries (SSBs) have been proposed as the next generation of batteries to address these limitations. Despite rapid development in this field, most solid-state lithium-ion conductors (SSLICs) remain far from practical application. Moreover, many state-of-the-art oxide SSLICs, such as Li7La3Zr2O, are still in the early stages of development. 12 The presence of rare earth elements or noble metals can increase the cost of solid electrolytes. Therefore, the discovery of new oxide SSLICs with elements exhibiting high room-temperature ionic conductivity and lower cost is desirable.

[0029] The inventors have discovered a solid ion conductor with high ionic conductivity, which is useful as a solid electrolyte in solid-state batteries. The disclosed solid ion conductor has a sodalite-type structure.

[0030] Therefore, solid-state ionic conductors comprising compounds of formula (I) are disclosed:

[0031] Li 4+(b-a)y+cδ+(a-γ)x M 1 3-x+y M 2 3-y M” x O 12 X 1 c X 2 1-c Formula (I)

[0032] In equation (I), M 1 M is a cationic element with oxidation state a, where a is +2 or +3; 2 M is a cationic element with an oxidation state b, where b is +4 or +5; the condition is that when M 1 When M is a cation element with an oxidation state of +2 a, 2 It is a cationic element with an oxidation state of +5, and when M 1 When M is a cation element with an oxidation state of +3 (a), 2is a cationic element with an oxidation state of +4; M'' is a cationic element with an oxidation state γ, where γ is less than b; X 1 is a cluster anion with an oxidation state of (-1-δ), where δ is 0 or 1; X 2 is a halogen; 0<c≤1; 0≤x≤1; and 0≤y≤2, with the proviso that when M 1 is a cationic element with an oxidation state a of +2 and M 2 is a cationic element with an oxidation state of +5, 0≤y≤1.

[0033] In formula (I), M 1 may be a cationic element with an oxidation state a of +3. For example, M 1 may be Al, B, Ga, In, Sc, Y, Fe, Mn, Co, Ni, La, Ce, Pr, Nd, Sm, Eu, Gd, Dy, Ho, Er, Lu, or a combination thereof. In one aspect, M 1 is Al. In formula (I), M 1 may be a cationic element with an oxidation state a of +2. For example, M 1 may be Mg, Ca, Sr, Ba, Co, Ni, Zn, Fe, or a combination thereof. In formula (I), M 2 may be a cationic element with an oxidation state b of +4. For example, M 2 may be Si, Ti, Zr, Hf, Ge, Sn, or a combination thereof. In one aspect, M 2 is Si. In formula (I), M 2 may be a cationic element with an oxidation state b of +5. For example, M 2 may be Nb, Ta, P, As, Sb, or a combination thereof.

[0034] As described above, when M 1 is a cationic element with an oxidation state a of +2, M 2 is a cationic element with an oxidation state of +5, and when M 1 is a cationic element with an oxidation state a of +3, M 2 is a cationic element with an oxidation state of +4. For example, when M 1 is Al, B, Ga, In, Sc, Y, Fe, Mn, Co, Ni, La, Ce, Pr, Nd, Sm, Eu, Gd, Dy, Ho, Er, Lu, or a combination thereof, then M 2 is Si, Ti, Zr, Hf, Ge, Sn, or a combination thereof. Alternatively, when M 1 is Mg, Ca, Sr, Ba, Co, Ni, Zn, Fe, or a combination thereof, then M 2is Nb, Ta, P, As, Sb, or a combination thereof. In one aspect, M 1 is Al and M 2 is Si.

[0035] In one aspect, M 1 may be a cationic element with an oxidation state a of +3 and M 2 may be a cationic element with an oxidation state b of +4, and the solid ionic conductor has the formula (IA)

[0036] Li 4+y+cδ+(3-γ)x M +3 3-x+y M +4 3-y M” x O 12 X 1 c X 2 1-c Formula (IA).

[0037] In one aspect, M 1 may be a cationic element with an oxidation state a of +2 and M 2 may be a cationic element with an oxidation state b of +5, and the solid ionic conductor has the formula (IB)

[0038] Li 4+3y+cδ+(2-γ)x M +2 3-x+y M +5 3-y M” x O 12 X 1 c X 2 1-c Formula (IB).

[0039] In one aspect, in formula (I), x=0. Therefore, when x=0, M” is absent in the compound of formula (I). In one aspect, in formula (I), 0<x≤1. When present, M” is a cationic element with an oxidation state γ, wherein γ is less than b. For example, when b is +5, M” may have an oxidation state γ of +1, +2, +3, or +4, and when b is +4, M” may have an oxidation state γ of +1, +2, or +3. In one aspect, M” may be Al, B, Ga, In, Sc, Y, Fe, Mn, Co, Ni, La, Ce, Pr, Nd, Sm, Eu, Gd, Dy, Ho, Er, Lu, Be, or a combination thereof. Be is specifically mentioned.

[0040] X in formula (I) 1is a cluster anion with an oxidation state of (-1-δ), wherein δ is 0 or 1. In one aspect, δ is 0 and X 1 has an oxidation state of -1. In one aspect, δ is 1 and X 1 has an oxidation state of -2. The cluster anion with an oxidation state of -1 may also be referred to as a pseudohalogen. In one aspect, X 1 may be a pseudohalogen, and the pseudohalogen includes BH4 - , BF4 - , AlH4 - , OH - , SH - , NH2 - , or a combination thereof. In one aspect, X 1 may be a pseudohalogen, and the pseudohalogen includes BH4 - , BF4 - , AlH4 - , SH - , NH2 - , or a combination thereof. In one aspect, X 1 may be a pseudohalogen, and the pseudohalogen includes BH4 - , BF4 - , SH - , NH2 - , or a combination thereof. In one aspect, X 1 may be a pseudohalogen, and the pseudohalogen includes BH4 - , BF4 - , SH - , or a combination thereof. In one aspect, X 1 may be a pseudohalogen, and the pseudohalogen includes SH - . In one aspect, X 1 may be a cluster anion with an oxidation state of -2, such as S 2- , SO4 2- , or a combination thereof.

[0041] The content of the cluster anion may satisfy 0<c≤1. In one aspect, c=1. In one aspect, 0.01≤c≤1, or 0.1≤c≤1, or 0.1≤c≤0.9, or 0.1≤c≤0.75, or 0.1≤c≤0.5, or 0.1≤c≤0.25.

[0042] When c<1, X 2 is present in an amount of 1-c. X in formula (I) 2 is a halogen, and thus may be F - , Cl - , Br - , I - , or a combination thereof. Particular mention is made of Cl - and Br- In one respect, X 2 For Cl - In one respect, halogens are not present in the compounds of formula (I).

[0043] In one specific aspect, x = 0 and the compound has the formula

[0044] Li 4+(b-a)y+cδ M 1 3+y M 2 3-y O 12 X 1 c X 2 1-c

[0045] Where M 1 M 2 X 1 X 2 a, b, c, and δ are as defined above. For example, M 1 It can be a cationic element with an oxidation state of +3; M 2 It can be a cation element with an oxidation state of +4; y can be 1; X 1 It can be BH4 - BF4 - AlH4 - OH - SH - NH2 - S 2- SO4 2- , or combinations thereof; and c can be 1. For example, M 1 It can be Al, B, Ga, In, Sc, Y, Fe, Mn, Co, Ni, La, Ce, Pr, Nd, Sm, Eu, Gd, Dy, Ho, Er, Lu, or combinations thereof; M 2 It can be Si, Ti, Zr, Hf, Ge, Sn, or a combination thereof; y can be 1; X 1 It can be BH4 - BF4 - AlH4 - OH - SH - NH2 - S 2- SO4 2- , or combinations thereof; and c can be 1. For example, M 1 Can be Al; M 2 It can be Si; y can be 1; X 1 It can be BH4 - BF4 -AlH4 - OH - SH - NH2 - S 2- SO4 2- , or combinations thereof; and c can be 1.

[0046] In one aspect, the solid-state ionic conductor may include, but is not limited to, Li5Al4Si2O 12 BH4, Li5Al4Si2O 12 SH, Li5Al4Si2O 12 NH2, Li5Al4Si2O 12 AlH4, Li5Al4Si2O 12 BF4, Li6Al3Si2BeO 12 (BH4), Li5Al4Si2O 12 (BH4) 0.5 Cl 0.5 Li5Al4Si2O 12 (NH2) 0.5 Cl 0.5 、and Li 4.5 Al3Si3O 12 (Cl) 0.5 (SO4) 0.5 .

[0047] The solid-state ionic conductor can have a strength equal to or greater than 1 × 10⁻⁶ at 300 Kelvin (K). -4 Ionic conductivity of millisiemens per centimeter (mS / cm). For example, the solid-state ionic conductor can have 1 × 10⁻⁶ at 300 K. -4 mS / cm to 1×10 2 mS / cm, 1×10 -4 mS / cm to 40mS / cm, 1×10 -4 mS / cm to 30mS / cm, 1×10 -4 mS / cm to 25mS / cm, 1×10 -4 mS / cm to 10mS / cm, 1×10 -4 mS / cm to 8mS / cm, 1×10 -4 mS / cm to 1mS / cm, or 1×10 -2Ionic conductivity ranging from mS / cm to 1 mS / cm. Ionic conductivity can be measured at 300 K by the complex impedance method, and further details can be found in J.-M. Winand et al., “Measurement of Ionic Conductivity in Solid Electrolytes,” Europhysics Letters, Vol. 8, No. 5, pp. 447-452, 1989, the contents of which are incorporated herein by reference in their entirety.

[0048] In one specific aspect, M 1 For Al, M 2 Let Si be an integer, x = 0, c = 1, and X be an integer. 1 The solid ionic conductor is BH4, and has the formula Li5Al4Si2O. 12 BH4. When the solid-state ionic conductor is Li5Al4Si2O 12 In BH4, the ionic conductivity can be 1×10⁻⁶. -4 mS / cm to 1×10 2 mS / cm, or 1mS / cm to 1×10 2 mS / cm, or 1mS / cm to 10mS / cm.

[0049] In one specific aspect, M 1 For Al, M 2 Let Si be an integer, x = 0, c = 1, and X be an integer. 1 The solid ionic conductor is SH, and has the formula Li5Al4Si2O 12 SH. When the solid-state ionic conductor is Li5Al4Si2O 12 At SH, the ionic conductivity can be 1×10⁻⁶. -4 mS / cm to 1×10 2 mS / cm, or 1mS / cm to 1×10 2 mS / cm, or 1mS / cm to 30mS / cm.

[0050] In one specific aspect, M 1 For Al, M 2 Let Si be an integer, x = 0, c = 1, and X be an integer. 1 The solid ionic conductor is NH2 and has the formula Li5Al4Si2O 12 NH2. When the solid ionic conductor is Li5Al4Si2O 12 In NH2, the ionic conductivity can be 1×10⁻⁶. -4 mS / cm to 1×10 2 mS / cm, or 1×10 -2 mS / cm to 1mS / cm.

[0051] In one specific aspect, M 1 For Al, M 2 Let Si be an integer, x = 0, c = 1, and X be an integer. 1 The solid ionic conductor is AlH4, and has the formula Li5Al4Si2O 12 AlH4. When the solid-state ionic conductor is Li5Al4Si2O 12 In AlH4, the ionic conductivity can be 1×10⁻⁶. -4 mS / cm to 1×10 2 mS / cm.

[0052] In one specific aspect, M 1 For Al, M 2 Let Si be an integer, x = 0, c = 1, and X be an integer. 1 The solid ionic conductor is BF4, and has the formula Li5Al4Si2O. 12 BF4. When the solid-state ionic conductor is Li5Al4Si2O 12 In BF4, the ionic conductivity can be 1×10⁻⁶. -4 mS / cm to 1×10 2 mS / cm, or 1×10 -2 mS / cm to 1mS / cm.

[0053] A method for manufacturing the solid-state ionic conductor is also disclosed. The solid-state ionic conductor can be prepared using a wet synthesis method. For example, the solid-state ionic conductor can be prepared by using a precursor compound, such as a lithium compound, M... 1 Precursor, M 2 Precursor, X 1 Precursor, and optionally M" precursor and optionally X 2 The precursor is contacted in stoichiometric amounts with a suitable stoichiometric mixture of elements to provide a solid ionic conductor of the product, and then the mixture is processed to provide a solid ionic conductor of formula (I). For example, the lithium precursor may be LiNO3 or LiOH, M 1 The precursor can be M 1 O, M 1 2O3, M 1 (OH)2, M 1 (OH)3, M 1 (NO3)2, or M 1 (NO3)3, M 2 The precursor can be M 2 O2, M 2 2O5, Li2M 2 O3, Li3M 2 O4, M 2 (NO3)4, or M 2(NO3)5, X 1 The precursor can be LiX 1 or Li2X 1 The precursor of M (when present) can be M”O, M”2O3, M”(OH)2, M”(OH)3, M”(NO3)2, or M”(NO3)3, and X 2 The precursor (if present) can be LiX 2 .

[0054] The processing may include any suitable method, such as hydrothermal synthesis, solvothermal synthesis, or microwave synthesis. The hydrothermal and solvothermal synthesis may be carried out at suitable temperatures, such as 100°C-200°C, 200°C-250°C, or 250°C-300°C, using any suitable solvent such as water, ethylene glycol, 1-butanol, 1-hexanol, 1-octanol, 1-decanol, or combinations thereof, for effective times, such as 0.5-20 hours, 2-48 hours, 3-180 hours, 0.5-2 hours, or 0.7-1 hour, for providing the solid-state ionic conductor.

[0055] The microwave synthesis can be performed at a suitable temperature, such as 100°C-200°C, 200°C-250°C, or 250°C-300°C, using any suitable solvent such as water, ethylene glycol, 1-butanol, 1-hexanol, 1-octanol, 1-decanol, or combinations thereof. Reference is made to using microwaves with frequencies of 2.45 GHz-915 MHz for 10-60 minutes or 1-30 hours.

[0056] The disclosed method provides desired ionic conductivity and stability, for example, relative to Li / Li + A solid-state ionic conductor with stability of 1.5 volts (V) to 5 V, for example 1.75 V to 4.8 V, 2 V to 4.6 V, or 2.5 V to 4.4 V. In one aspect, the solid-state ionic conductor is at least kinetically stable when in contact with lithium transition metal oxide cathode active materials such as lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide, or lithium transition metal phosphate cathode active materials such as lithium iron phosphate, or at least kinetically stable when in contact with lithium metal, for example, the solid-state ionic conductor does not form alloys or compounds when in contact with lithium metal.

[0057] The solid-state ion conductor can be disposed on the positive electrode active material layer to provide an illustrative illustration. Figure 1The protected positive electrode comprises: a current collector 101, a positive electrode active material layer 102, and a protective layer 103 including the solid-state ionic conductor on the positive electrode active material layer. While not wishing to be bound by theory, it is understood that the use of a protective layer including the solid-state ionic conductor can prevent degradation of the positive electrode active material, resulting in improved performance. The protective layer can be formed on the positive electrode active material layer, for example, by sputtering, or by casting or coating the positive electrode active material layer with a coating composition including the solid-state ionic conductor and drying to remove the solvent from the coating composition.

[0058] The solid-state ion conductor is disposed on the negative electrode active material layer to provide an illustrative representation. Figure 2 The protected negative electrode comprises: a negative electrode active material layer 201 disposed on a current collector 202, and a protective layer 203 comprising the solid-state ionic conductor disposed on the negative electrode active material layer. While not wishing to be bound by theory, it is understood that the use of a protective layer comprising the solid-state ionic conductor can prevent degradation of the negative electrode active material, resulting in improved performance. The protective layer can be disposed on the negative electrode active material layer, for example, by sputtering, or by casting or coating the negative electrode active material layer with a coating composition comprising the solid-state ionic conductor and drying to remove the solvent of the coating composition.

[0059] In one aspect, the solid-state ion conductor may alternatively be disposed on the current collector to provide a negative electrode. The solid-state ion conductor may be disposed on the current collector by, for example, sputtering, or by, for example, casting or coating the current collector with a coating composition comprising the solid-state ion conductor and drying to remove the solvent of the coating composition.

[0060] An electrochemical battery (e.g., a lithium battery) is also disclosed, comprising: a positive electrode, a negative electrode, and an electrolyte layer between the positive electrode and the negative electrode, wherein at least one of the positive electrode, negative electrode, or electrolyte layer comprises a solid-state ion conductor as described in this disclosure. For example, the solid-state ion conductor may be disposed between the positive and negative electrodes of a lithium battery and may be used as a solid electrolyte in a lithium battery, schematically shown in… Figure 3 middle. Figure 3The lithium battery shown in includes: a positive electrode comprising a positive electrode active material layer 301 on a positive electrode current collector 302, an electrolyte layer 303, and a negative electrode comprising a negative electrode active material layer 304 on a negative electrode current collector 305. It is understood that the positive electrode may alternatively be referred to as a cathode, and the negative electrode may alternatively be referred to as an anode. The electrolyte layer may include the solid ionic conductor. In one aspect, the electrolyte layer is suitably electrically insulating to function as a separator that electrically isolates the positive electrode from the negative electrode. For the positive electrode current collector, aluminum or stainless steel may be used, and for the negative electrode current collector, copper, stainless steel, or titanium may be used.

[0061] The electrolyte layer may alternatively or additionally include a solid electrolyte different from or in addition to the solid ionic conductor. The solid electrolyte may include, for example, an oxide solid electrolyte or a sulfide solid electrolyte.

[0062] Examples of the oxide solid electrolyte may include Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (where 0<x<2 and 0≤y<3); BaTiO3; Pb(Zr a Ti 1-a )O3(PZT), where 0≤a≤1; Pb 1-x La x Zr 1-y Ti y O3(PLZT), where 0≤x<1 and 0≤y<1; Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3(PMN-PT); HfO2; SrTiO3; SnO2; CeO2; Na2O; MgO; NiO; CaO; BaO; ZnO; ZrO2; Y2O3; Al2O3; TiO2; SiO2; Li3PO4; Li x Ti y (PO4)3(where 0<x<2 and 0<y<3); Li x Al y Ti z (PO4)3 where 0<x<2, 0<y<1, and 0<z<3; Li 1+x+y (Al a Ga 1-a ) x (Ti b Ge 1-b ) 2-x Si y P 3-y O12 , where 0≤x≤1, 0≤y≤1, 0≤a≤1, and 0≤b≤1; Li x La y TiO3, where 0<x<2 and 0<y<3; Li2O; LiOH; Li2CO3; LiAlO2; Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2; or Li 3+x La3M2O 12 where M is Te, Nb, or Zr, and 0≤x≤10. Lithium garnets such as Li7La3Zr2O are also mentioned 12 (LLZO) or Li 3+x La3Zr 2-a Me a O 12 (for example, Me-doped LLZO, where Me is Ga, W, Nb, Ta, or Al, and 0≤x≤10 and 0≤a<2). Combinations comprising at least two of the foregoing may be used.

[0063] Examples of the sulfide solid electrolyte may include Li2S-P2S5, Li2S-P2S5-LiX (where X is halogen), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z where m and n are each a positive number, and Z represents any one of Ge, Zn and Ga m S n , Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MeO q (where p and q are each a positive number, and Me represents at least one of P, Si, Ge, B, Al, Ga, or In), Li 7-x PS 6-x Cl x (where 0≤x≤2), Li 7-x PS 6-x Br x (where 0≤x≤2), or Li 7-x PS 6-x I x(Where 0 ≤ x ≤ 2). The sulfide solid electrolyte may include at least sulfur (S), phosphorus (P), and lithium (Li) as constituent elements in the sulfide solid electrolyte material. For example, the sulfide solid electrolyte may be a material comprising Li₂S-P₂S₅. Here, when a material comprising Li₂S-P₂S₅ is used as the sulfide solid electrolyte material, the molar ratio of Li₂S to P₂S₅ (Li₂S:P₂S₅) may be selected, for example, in the range of about 50:50 to about 90:10. The sulfide solid electrolyte may also include a sulfide-germanium ore type solid electrolyte, such as Li 7-x PS 6-x Cl x (where 0≤x≤2), Li 7-x PS 6-x Br x (where 0≤x≤2), or Li 7-x PS 6-x I x (where 0≤x≤2), for example, Li6PS5Cl, Li6PS5Br, or Li6PS5I.

[0064] The electrolyte layer comprising the solid ionic conductor may be non-porous or have a porosity of 0% (non-porous) to 25% based on the total volume of the electrolyte layer. The porosity may be, for example, 0%-25%, 1%-20%, 5%-15%, or 7%-12% based on the total volume of the electrolyte layer. The porosity of the electrolyte layer can be determined by scanning electron microscopy, the details of which can be determined by those skilled in the art without excessive experimentation. Alternatively, the porosity can be determined using nitrogen isotherms as disclosed in EP Barrett, LG Joyner, PP Halenda, “The determination of pore volume and area distributions in porous substances. I. Computations from nitrogen isotherms,” J. Am. Chem. Soc. (1951), 73, 373-380, the details of which can be determined by those skilled in the art without excessive experimentation.

[0065] In one aspect, the electrolyte layer is porous, and an ionic liquid, a polymeric ionic liquid, a liquid electrolyte comprising a lithium salt and an organic solvent, or a combination thereof, is disposed in the pores of the electrolyte layer to provide a hybrid electrolyte.

[0066] The ionic liquid (e.g., molten salt) may include: i) ammonium cations, pyrrolidines Cations, Pyridine Ions, pyrimidines Cationic, imidazole Cations, piperidine cationic, pyrazole cation, azole cationic, pyridazine cation, Cation, Sulfonate, Triazole ii) cations, or combinations thereof, and ii) anions, such as BF4 - PF6 - AsF6 - SbF6 - AlCl4 - HSO4 - ClO4 - CH3SO3 - CF3CO2 - Cl - ,Br - I - SO4 2- CF3SO3 - (FSO2)2N - (C2F5SO2)2N - (C2F5SO2)(CF3SO2)N - (CF3SO2)2N - or combinations thereof. Examples of said ionic liquids include bis(trifluoromethanesulfonyl)imide N-methyl-N-propylpyrrolidine. bis(trifluoromethanesulfonyl)imide N-butyl-N-methyl-pyrrolidine bis(trifluoromethanesulfonyl)imide 1-butyl-3-methyl-imidazolium bis(trifluoromethanesulfonyl)imide 1-ethyl-3-methyl-imidazolium , or combinations thereof.

[0067] The polymeric ionic liquid may be a polymerization product of an ionic liquid monomer or a polymer compound. The polymeric ionic liquid may include repeating units, which include: i) ammonium cations and pyrrolidines. Cations, Pyridine Ions, pyrimidines Cationic, imidazole Cations, piperidine cationic, pyrazole cation, azole cationic, pyridazine cation, Cation, Sulfonate, Triazole ii) cations, or combinations thereof, and ii) anions, such as BF4 - PF6 - AsF6 - SbF6 - AlCl4 - HSO4 - ClO4 - CH3SO3 - CF3CO2 - (CF3SO2)2N - (FSO2)2N - Cl - ,Br - I - SO4 2- CF3SO3 - (C2F5SO2)2N - (C2F5SO2)(CF3SO2)N - NO3 - Al2Cl7 - (CF3SO2)3C - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - SF5CF2SO3 - SF5CHFCF2SO3 - CF3CF2(CF3)2CO - (CF3SO2)2CH - (SF5)3C - 、(O(CF3)2C2(CF3)2O)2PO - , or combinations thereof.

[0068] For liquid electrolytes comprising a lithium salt and an organic solvent, the lithium salt may be BF4. - PF6 - AsF6 - SbF6 - AlCl4 - HSO4 - ClO4 - CH3SO3 - CF3CO2 - (CF3SO2)2N - (FSO2)2N - Cl - ,Br -I - SO4 2- CF3SO3 - (C2F5SO2)2N - (C2F5SO2)(CF3SO2)N - NO3 - Al2Cl7 - (CF3SO2)3C - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - SF5CF2SO3 - SF5CHFCF2SO3 - CF3CF2(CF3)2CO - (CF3SO2)2CH - (SF5)3C - 、(O(CF3)2C2(CF3)2O)2PO - Lithium salts, or combinations thereof. The organic solvent may include carbonates such as propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butyl carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, or combinations thereof.

[0069] The electrolyte layer may further include a separator membrane. The separator membrane may be electrically insulating and may include polyethylene, polypropylene, polyvinylidene fluoride, or combinations thereof. For example, the separator membrane may be a multilayer separator membrane, such as a double-layer separator of polyethylene / polypropylene, a triple-layer separator of polyethylene / polypropylene / polyethylene, or a triple-layer separator of polypropylene / polyethylene / polypropylene. The separator membrane may have a pore size of 0.01 μm-10 μm and a thickness of 5 μm-20 μm. If present, the liquid electrolyte, ionic liquid, or polymeric ionic liquid electrolyte may be disposed within the pores of the separator membrane.

[0070] In one aspect, other electrolytes, including liquid electrolytes or ionic liquid (e.g., molten salt) electrolytes, may be excluded from the disclosed electrolyte layer.

[0071] The electrolyte layer can have any suitable thickness. The thickness of the solid electrolyte layer can be 1-300 μm, 2-100 μm, or 30-60 μm.

[0072] The positive electrode includes a positive electrode active material layer comprising lithium transition metal oxide, lithium transition metal phosphate, or a combination thereof. For example, the positive electrode active material may be a compound represented by any of the following: Li a M1 l-b M 2 b D2, where 0.90 ≤ a ≤ 1.8 and 0 ≤ b ≤ 0.5; Li a E l-b M 2 b O 2-c D c Where 0.90≤a≤1.8, 0≤b≤0.5, and 0≤c≤0.05; LiE 2-b M 2 b O 4-c D c Where 0 ≤ b ≤ 0.5 and 0 ≤ c ≤ 0.05; Li a Ni 1-b-c Co b M 2 c D α Where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2; Li a Ni l-b-c Co b M 2 c O 2-α X α Where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2; Li a Ni 1-b-c Co b M 2 c O 2-α X2, where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2; Li a Ni 1-b-c Mn b M 2 c D α Where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α≤2; Li a Ni 1-b- c Mn b M 2 c O 2-a X α Where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2; Li a Ni 1-b-c Mn b M2 c O 2-α X2, where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, and 0<α<2; Li a Ni b E c G d O2, where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, and 0.001≤d≤0.1; Li a Ni b Co c Mn d G e O2, where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, and 0.001≤e≤0.1; Li a NiG b O2, where 0.90≤a≤1.8 and 0.001≤b≤0.1; Li a CoG b O2, where 0.90≤a≤1.8 and 0.001≤b≤0.1; Li a MnG b O2, where 0.90≤a≤1.8 and 0.001≤b≤0.1; Li a Mn2G b O4, where 0.90≤a≤1.8 and 0.001≤b≤0.1; QO2; QS2; LiQS2; V2O5; LiV2O2; LiRO2; LiNiVO4; Li (3-f) J2(PO4)3(0≤f≤2); Li (3-f) Fe2(PO4)3, where 0≤f≤2; or LiFePO4, wherein in the aforementioned positive electrode active material, M 1 is Ni, Co, or Mn; M 2 is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, or a rare earth element; D is O, F, S, or P; E is Co or Mn; X is F, S, or P; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, or V; Q is Ti, Mo or Mn; R is Cr, V, Fe, Sc, or Y; and J is V, Cr, Mn, Co, Ni, or Cu. Examples of the positive electrode active material include LiCoO2, LiMn where x=1 or 2 x O 2x , LiNi where 0<x<1 1-x Mn x O2, LiNi where 0≤x≤0.5 and 0≤y≤0.5 1-x-y Co xMn y O2, where 0 ≤ x ≤ 0.5 and 0 ≤ y ≤ 0.5, LiNi 1-x-y Co x Al y O2, LiFePO4, TiS2, FeS2, TiS3, or Fe2S3. For example, the positive electrode active material may include NMC 811 (LiNi). 0.8 Mn 0.1 Co 0.1 O2), NMC 622(LiNi) 0.6 Mn 0.2 Co 0.2 O2), NMC532(LiNi 0.5 Mn 0.3 Co 0.2 O2), or NCA (LiNi) 0.8 Co 0.15 Al 0.05 O2).

[0073] The positive electrode active material layer may further include a binder. The binder promotes adhesion between the components of the positive electrode active material layer and adhesion of the positive electrode active material layer to the current collector. Examples of the binder may include polyacrylic acid (PAA), polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluorinated rubber, copolymers thereof, or combinations thereof. The amount of the binder may be in the range of 1 part by weight to 10 parts by weight, for example, in the range of 2 parts by weight to 7 parts by weight, based on the total weight of 100 parts by weight of the positive electrode active material. When the amount of the binder is in the above range, for example, 1 part by weight to 10 parts by weight, the adhesion of the electrode to the current collector may be suitably strong.

[0074] The positive electrode active material layer may further include a conductive agent. Any suitable conductive agent may be used. The conductive agent may include carbon, metal, or oxide. The carbon may include carbon black, carbon fiber, graphite, carbon nanotube, graphene, or a combination thereof. The carbon black may be, for example, acetylene black, Ketjen black, Super P carbon, channel black, furnace black, lamp black, pyrolytic carbon black, or a combination thereof. The graphite may be natural graphite or artificial graphite. The metal may include a metal element such as nickel, and may be in the form of fiber or powder, for example, aluminum powder or nickel powder. The conductive agent may include an oxide such as zinc oxide or potassium titanate; or a conductive polymer such as polyethylene oxide or a polyphenylene derivative. A combination including at least two of the foregoing conductive agents may be used. The amount of the conductive agent may be about 1 part by weight to about 10 parts by weight, for example, about 2 parts by weight to about 5 parts by weight, based on 100 parts by weight of the total weight of the positive electrode active material.

[0075] The positive electrode active material layer may further include the solid ionic conductor, or alternatively or additionally include a solid electrolyte different from or in addition to the solid ionic conductor. The solid electrolyte may include, for example, the oxide solid electrolyte, the sulfide solid electrolyte, or a combination thereof.

[0076] The positive electrode active material layer may be disposed on the surface of a substrate such as an aluminum foil current collector using any suitable method, for example, using tape casting, slurry casting (i.e., slurry coating), or screen printing. Additional details of tape casting, slurry coating, and screen printing, such as suitable binders and solvents, may be determined by those skilled in the art without undue experimentation. For example, N-methylpyrrolidone may be used as the solvent.

[0077] The positive electrode active material layer may have any suitable thickness, for example, a thickness of 1-300 μm, 2 μm-100 μm, or 30-60 μm.

[0078] The negative electrode may include a negative electrode active material layer on a current collector. The negative electrode active material layer may include carbon, non-transition metal oxide, lithium metal, lithium metal alloy, or a combination thereof. The carbon may include natural graphite or artificial graphite, each of which may be crystalline or amorphous. Examples of amorphous carbon include soft carbon, hard carbon, mesocarbon (mesophase carbon), mesophase pitch carbon, and calcined coke. The non-transition metal oxide may include SnO where 0<x≤2 x , or SiO where 0<x≤2 xThe lithium metal alloy used for the negative electrode may include lithium, and metals or metalloids that can be alloyed with lithium. Examples of metals or metalloids that can be alloyed with lithium include Si, Sn, Al, Ge, Pb, Bi, Sb, Si-Y' alloys (where Y' is at least one of the following: alkali metal, alkaline earth metal, group 13-16 element, transition metal, or rare earth element, other than Si), or Sn-Y' alloys (where Y' is at least one of the following: alkali metal, alkaline earth metal, group 13-16 element, transition metal, or rare earth element, other than Sn). Y' can be Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, or combinations thereof. The current collector used for the negative electrode can be, for example, copper or titanium.

[0079] The negative electrode active material layer may include the binders further disclosed above. The negative electrode active material layer may be applied to the surface of a substrate, such as a copper or titanium foil current collector, using any suitable method, such as tape casting, paste casting, or screen printing. Further details regarding tape casting, paste coating, and screen printing, such as suitable binders and solvents, can be determined by those skilled in the art without excessive experimentation. For example, N-methylpyrrolidone can be used as the solvent.

[0080] The negative electrode active material layer may further include the solid ion conductor, or alternatively or additionally include a solid electrolyte different from or other than the solid ion conductor. The solid electrolyte may include, for example, the oxide solid electrolyte, the sulfide solid electrolyte, or a combination thereof.

[0081] The negative electrode can be of the "anode-free" or "non-anode-type" form in which lithium is not initially present in the negative electrode. In the "anode-free" negative electrode, the negative electrode may initially include a current collector and a solid electrolyte on the current collector, for example, a solid ionic conductor of formula (I), or alternatively at least one of the oxide solid electrolyte or the sulfide solid electrolyte, or the solid ionic conductor of formula (I) further comprising at least one of the oxide solid electrolyte or the sulfide solid electrolyte. In one aspect, the solid ionic conductor, the solid electrolyte, or a combination thereof are directly on the current collector. Charging the battery allows lithium to be deposited to form a negative electrode active material layer on the current collector, for example, to deposit lithium metal or form a lithium metal alloy on the current collector. The solid ionic conductor of formula (I), or alternatively at least one of the oxide solid electrolyte or the sulfide solid electrolyte, or the solid ionic conductor of formula (I) further comprising at least one of the oxide solid electrolyte or the sulfide solid electrolyte, can be disposed on the current collector by, for example, sputtering or coating.

[0082] The lithium battery can be manufactured by providing the positive electrode, providing the negative electrode, and disposing a solid-state ion conductor comprising a compound according to formula (I) between the positive electrode and the negative electrode. For example, the lithium battery can be manufactured by sputtering a solid-state ion conductor comprising a compound according to formula (I) onto the positive electrode active material layer, disposing a negative electrode thereon, winding or folding the resulting structure, and then sealing the wound or folded structure into a cylindrical or rectangular battery case or bag to provide a lithium battery.

[0083] The present disclosure is further illustrated by the following non-limiting embodiments.

[0084] Example

[0085] Ion conductivity analysis

[0086] The ionic conductivity of several compounds according to formula (I) was determined using ab initio molecular dynamics (AIMD) calculations using the Vienna Ab initio Simulation Package. Relevant parameters for the calculations included the projected augmented wave potential with a kinetic energy cutoff of 400 eV, the exchange and correlation functional of the Perdew-Burke-Ernzerhof generalized gradient (GGA-PBE), and a simulation time of 200 picoseconds with a 2 femtosecond time step. For comparison, the conductivity of Li5Al4Si2O was also determined. 12 Br, Li5Al4Si2O 12 Cl, and Li5Al4Si2O 12 Ionic conductivity of I.

[0087] Figure 4 The figure shown is Li5Al4Si2O as a comparative example. 12 Arrhenius plot of the simulation results for Br. The activation energy is 0.211 eV and the ionic conductivity at 300 K is 7.116 mS / cm.

[0088] Figure 5 The figure shown is Li5Al4Si2O as a comparative example. 12 Arrhenius plot of simulation results for Cl. The activation energy is 0.448 eV and the ionic conductivity at 300 K is 0.017 mS / cm.

[0089] Figure 6 The figure shown is Li5Al4Si2O as a comparative example. 12 I. Arrhenius plot of simulation results. The activation energy is 0.232 eV and the ionic conductivity at 300 K is 4.067 mS / cm.

[0090] Figure 7 The value shown is Li5Al4Si2O 12 Arrhenius plot of simulation results for BH4. The activation energy is 0.220 eV and the ionic conductivity at 300 K is 5.664 mS / cm.

[0091] Figure 8 The value shown is Li5Al4Si2O 12 Arrhenius plot of SH simulation results. The activation energy is 0.151 eV and the ionic conductivity at 300 K is 27.1 mS / cm.

[0092] Figure 9 The value shown is Li5Al4Si2O 12 Arrhenius plot of simulation results for NH2. The activation energy is 0.334 eV and the ionic conductivity at 300 K is 0.218 mS / cm.

[0093] Figure 10 The value shown is Li5Al4Si2O 12 Arrhenius plot of simulation results for AlH4. The activation energy is 0.457 eV and the ionic conductivity at 300 K is 1.70 × 10⁻⁶. -2 mS / cm.

[0094] Figure 11 The value shown is Li5Al4Si2O 12 Arrhenius plot of simulation results for BF4. The activation energy is 0.319 eV and the ionic conductivity at 300 K is 0.291 mS / cm.

[0095] In lithium-ion conductivity and anion (e.g., X) 1 The relationship between the dimensions is shown in Figure 12 And in Table 1. By Figure 12 As shown in Table 1, the ionic conductivity increases with the anion (X). 1 The size increases to a certain point (e.g., to approximately). The ionic conductivity then appears to decrease as the anion size continues to increase.

[0096] Table 1

[0097] <![CDATA[Li4Al3Si3O 12 Cl]]> <![CDATA[<10 -6 ]]> <![CDATA[Li5Al4Si2O 12 Cl]]> 0.017 <![CDATA[Li5Al4Si2O 12 Br]]> 7.116 <![CDATA[Li5Al4Si2O 12 I]]> 4.069 <![CDATA[Li5Al4Si2O 12 BH4]]> 5.664 <![CDATA[Li5Al4Si2O 12 BF4]]> 0.291 <![CDATA[Li5Al4Si2O 12 AlH4]]> <![CDATA[1.7×10 -2 ]]> <![CDATA[Li5Al4Si2O 12 OH]]> <![CDATA[<10 -8 ]]> <![CDATA[Li5Al4Si2O 12 SH]]> 27.1 <![CDATA[Li5Al4Si2O 12 NH2]]> 0.218

[0098] These results demonstrate that the compound of formula (I) provides an unexpectedly improved lithium-ion conductivity. Among the most surprising results is the achievement of high room-temperature ionic conductivity exceeding 25 mS / cm by at least partially replacing the halogen with a thiol.

[0099] The compounds described above can be prepared according to the following methods.

[0100] Example 1. Li5Al4Si2O 12 BH4

[0101] Stoichiometric amounts of LiOH, Al₂O₃, SiO₂, and LiBH₄ are combined to provide a mixture. This mixture is dissolved in water in a hydrothermal synthesis autoclave reactor and heat-treated at 120°C for 24 hours to provide Li₅Al₄Si₂O₄. 12 BH4. The product was analyzed by X-ray powder diffraction (XRD) under CuKα radiation, and the XRD analysis showed that Li5Al4Si2O was prepared. 12 BH4.

[0102] Li5Al4Si2O 12 The simulated crystal structure of BH4 is shown in Figure 13 In the middle, you can see O. 2- (1301), Li + (1302), Si 4+ (1303), Al 3+ (1304), and BH4 - The arrangement of (1305).

[0103] Li5Al4Si2O 12 The simulated XRD spectrum of BH4 is shown in Figure 14 In Chinese. For reference only. Figure 14 The image shows Li4Al3Si3O 12 Simulated XRD spectrum of Cl.

[0104] Example 2. Li5Al4Si2O 12 OH

[0105] Stoichiometric amounts of LiOH, Al2O3, and SiO2 were combined to provide a mixture. This mixture was dissolved in water in a quartz tube reactor and heat-treated at 120°C for 30 minutes with the assistance of a 2.45 GHz microwave to provide Li5Al4Si2O 12 OH. The product was analyzed by X-ray powder diffraction (XRD) under CuKα radiation. XRD analysis showed that Li5Al4Si2O was prepared. 12 OH.

[0106] Li5Al4Si2O 12 The simulated XRD spectrum of OH is shown in Figure 14 middle.

[0107] Several aspects have been shown in the accompanying drawings. However, the invention may be embodied in many different forms and should not be construed as limited to the aspects set forth herein. Rather, these aspects are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art. Similar reference numerals always refer to similar elements.

[0108] It will be understood that when an element is referred to as being "on" another element, it may be directly on said other element or there may be intermediate elements between them. Conversely, when an element is referred to as being "directly on" another element, there are no intermediate elements.

[0109] It will be understood that although the terms “first,” “second,” “third,” etc., may be used herein to describe various elements, components, regions, layers, or parts, these elements, components, regions, layers, or parts should not be limited by these terms. These terms are used only to distinguish one element, component, region, layer, or part from another. Therefore, without departing from the teachings herein, the “first element,” “component,” “region,” “layer,” or “part” discussed below may be referred to as a second element, component, region, layer, or part.

[0110] The terminology used herein is for descriptive purposes only and is not intended to be limiting. As used herein, the singular forms “a” and “the” are intended to include the plural forms, including “at least one”, unless the context clearly indicates otherwise. “At least one” will not be construed as limiting “a”. “Or” means “and / or”. It will be further understood that the terms “comprising” or “including” as used in this specification indicate the presence of the stated features, regions, integrals, steps, operations, elements, or components, but do not preclude the presence or addition of one or more additional features, regions, integrals, steps, operations, elements, components, or sets thereof.

[0111] For ease of description, spatial relative terms such as “below,” “under,” “lower,” “above,” “upper,” etc., may be used herein to describe the relationship of one element or feature to another element or feature as shown in the figures. It will be understood that, in addition to the orientation depicted in the figures, spatial relative terms are intended to cover different orientations of the device in use or operation. For example, if the device in the figures is flipped, an element described as “below” or “under” other elements or features will be oriented “above” other elements or features. Thus, the exemplary term “below” can cover both orientations above and below. The device may be oriented in other ways (rotated 90 degrees or in other orientations), and the spatial relative descriptive terms used herein will be interpreted accordingly.

[0112] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure pertains. It will be further understood that terms, such as those defined in common dictionaries, should be understood to have meanings consistent with their context in the relevant field and in this disclosure, and will not be interpreted in an idealized or overly formal sense unless clearly defined herein.

[0113] Exemplary aspects are described herein with reference to cross-sectional views as schematic representations of idealized aspects. Thus, deviations from the shape of the figures will be anticipated as a result of, for example, manufacturing techniques and / or tolerances. Therefore, the aspects described herein should not be construed as limited to the specific shape of the regions shown herein, but rather include deviations in shape caused, for example, by manufacturing processes. For example, regions illustrated or described as flat may typically have rough and / or non-linear characteristics. Furthermore, sharp corners in the figures may be rounded. Therefore, the regions illustrated in the figures are schematic in nature, and their shapes are not intended to illustrate the precise shape of the regions nor to limit the scope of the claims.

[0114] As used in this article, “oxidation state” is used to describe the form of the hypothetical charge that an atom would have if all bonds with atoms of different elements were 100% ionic and had no covalent components.

[0115] "Group" refers to a group in the periodic table of elements according to the International Union of Pure and Applied Chemistry ("IUPAC") Group 1-18 classification system.

[0116] Although specific aspects have been described, alternatives, modifications, variations, improvements, and substantial equivalents that are currently unforeseeable or could be unforeseeable by the applicant or others skilled in the art may conceive of. Therefore, the appended claims, as they are filed and as they may be modified, are intended to include all such alternatives, modifications, variations, improvements, and substantial equivalents.

Claims

1. Solid-state ionic conductors, including compounds of formula (I): Li 4+(b-a)y+cδ+(a-γ)x M 1 3+x+y M 2 3-y M'' x O 12 X 1 c X 2 1-c Formula (I) in, In equation (I), M 1 It is a cationic element with an oxidation state α, where α is +2 or +3; M 2 It is a cationic element with an oxidation state b, where b is +4 or +5; The condition is that when M 1 When M is a cation element with an oxidation state of +2 a, 2 It is a cationic element with an oxidation state of +5, and when M 1 When M is a cation element with an oxidation state of +3 (a), 2 It is a cationic element with an oxidation state of +4; M'' is a cationic element with an oxidation state γ, where γ is less than b; X 1 It is a cluster anion with an oxidation state of (-1-δ), where δ is 0 or 1; X 2 It is a halogen; 0 < c ≤ 1; 0 ≤ x ≤ 1; and 0 ≤ y ≤ 2, provided that when M 1 It is a cationic element with an oxidation state of +2 a and M 2 For cations with an oxidation state of +5, 0 ≤ y ≤ 1. Where, when M 2 When M is a cation element with an oxidation state of +4 b, 2 Including Si.

2. The solid-state ion conductor as claimed in claim 1, wherein M 1 It is a cationic element with an oxidation state of +3 and M 1 It is Al, B, Ga, In, Sc, Y, Fe, Mn, Co, Ni, La, Ce, Pr, Nd, Sm, Eu, Gd, Dy, Ho, Er, Lu, or combinations thereof.

3. The solid-state ion conductor as described in claim 2, wherein M 1 For Al.

4. The solid-state ion conductor as claimed in claim 1, wherein M 1 It is a cationic element with an oxidation state of +2 a and M 1 It is Mg, Ca, Sr, Ba, Co, Ni, Zn, Fe, or a combination thereof.

5. The solid-state ion conductor as claimed in claim 1, wherein M 2 Further including Ti, Zr, Hf, Ge, Sn, or combinations thereof.

6. The solid-state ionic conductor of claim 1, wherein when M 2 When M is a cation element with an oxidation state of +5, 2 It can be Nb, Ta, P, As, Sb, or a combination thereof.

7. The solid-state ionic conductor as claimed in claim 1, wherein x = 0.

8. The solid-state ionic conductor of claim 1, wherein 0 < x ≤ 1 and M'' is Al, B, Ga, In, Sc, Y, Fe, Mn, Co, Ni, La, Ce, Pr, Nd, Sm, Eu, Gd, Dy, Ho, Er, Lu, Be, or a combination thereof.

9. The solid-state ionic conductor of claim 1, wherein δ is 0 and the cluster anion X 1 It has an oxidation state of -1.

10. The solid-state ion conductor of claim 9, wherein X 1 The halogen is a pseudohalogen, and the pseudohalogen includes BH4. - BF4 - AlH4 - OH - , SH-, NH2 - , or a combination thereof.

11. The solid-state ionic conductor of claim 1, wherein δ is 1 and the cluster anion X 1 It has an oxidation state of -2, and X 1 Including S 2- SO4 2- , or a combination thereof.

12. The solid-state ionic conductor as claimed in claim 1, wherein c = 1.

13. The solid-state ionic conductor of claim 1, wherein 0 < c < 1 and X 2 It is F, Cl, Br, I, or a combination thereof.

14. The solid-state ion conductor of claim 1, wherein M 1 It is a cationic element with an oxidation state of +3 and M 2 It is a cation element with an oxidation state of +4 b, and the solid ionic conductor has formula (IA). Li 4+y+cδ+(3-γ)x M +3 3+x+y M +4 3-y M'' x O 12 X 1 c X 2 1-c Formula (IA).

15. The solid-state ion conductor of claim 1, wherein M 1 It is a cationic element with an oxidation state of +2 and M 2 It is a cation element with an oxidation state of +5 b, and the solid ionic conductor has the formula (IB). Li 4+3y+cδ+(2-γ)x M +2 3+x+y M +5 3-y M'' x O 12 X 1 c X 2 1-c Formula (IB).

16. The solid-state ion conductor of claim 1, wherein... M 1 For Al; M 2 For Si; x is 0; y is 1; X 1 BH4 - BF4 - AlH4 - OH - SH - NH2 - S 2- SO4 2- or combinations thereof; and c is 1.

17. A method for preparing a solid-state ionic conductor as described in any one of claims 1-16, the method comprising: To provide the mixture, the following contact method is used: Lithium compounds; M 1 Precursor; M 2 Precursor; and X 1 Precursor; and The mixture is processed to provide a compound of formula (I).

18. The method of claim 17, wherein the mixture further comprises an M'' precursor.

19. The method of claim 17, wherein the mixture further comprises X 2 Precursor.

20. Positive electrode, including: Including lithium transition metal oxides, lithium transition metal phosphates, or combinations thereof, as positive electrode active material layers; and A solid-state ion conductor as described in any one of claims 1-16 on the positive electrode active material layer.

21. Negative electrode, including: Including a negative electrode active material layer of lithium metal, lithium metal alloy, or a combination thereof; and A solid-state ion conductor as described in any one of claims 1-16 on the negative electrode active material layer.

22. A negative electrode for a lithium secondary battery, the negative electrode comprising: current collector; and A solid ion conductor as described in any one of claims 1-16 on the current collector.

23. Electrochemical cells, including: positive electrode; negative electrode; as well as The electrolyte layer between the positive electrode and the negative electrode; The positive electrode, negative electrode, or electrolyte layer at least one of the following includes a solid ion conductor as described in any one of claims 1-16.

Citation Information

Patent Citations

  • Anion-doped ion conductor material as well as preparation method and application thereof

    CN111370755A